2007
DOI: 10.1016/s1472-6483(10)61059-0
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin-releasing hormone antagonists for assisted conception: a Cochrane Review

Abstract: Gonadotrophin-releasing hormone (GnRH) antagonists suppress gonadotrophin secretion resulting in dramatic reduction in treatment cycle duration. Assuming comparable clinical outcomes, these benefits may justify changing the standard long GnRH agonist protocol to GnRH antagonist regimens. To evaluate the evidence, databases (e.g. Cochrane Library, MEDLINE, EMBASE) were electronically searched, hand searches were performed, and manufacturers in the field were contacted. Twenty-seven randomized controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 22 publications
8
97
0
14
Order By: Relevance
“…But these study did not consider the influence of LH on IVF outcome. Al-Inany et al [10] after evaluation of 27 randomized controlled trials that compared GnRH antagonist with long GnRH agonist protocol in all types of patients reported reduced stimulation and gonadotropin consumption with the antagonist protocol. Griesinger et al [11] including only PCOS patients in his meta-analysis indicates that the number of stimulation days were significantly decreased with GnRH antagonists multiple dose in comparison with GnRH agonist long protocol, though it was not associated with a significant reduction in gonadotropin total dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But these study did not consider the influence of LH on IVF outcome. Al-Inany et al [10] after evaluation of 27 randomized controlled trials that compared GnRH antagonist with long GnRH agonist protocol in all types of patients reported reduced stimulation and gonadotropin consumption with the antagonist protocol. Griesinger et al [11] including only PCOS patients in his meta-analysis indicates that the number of stimulation days were significantly decreased with GnRH antagonists multiple dose in comparison with GnRH agonist long protocol, though it was not associated with a significant reduction in gonadotropin total dose.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Al-Inany et al [9] metaanalysis revealed that GnRH antagonist gives significantly worse results than GnRH agonist in the general IVF population. However, most analyses demonstrate that GnRH antagonist protocols have certain advantages over agonists such as reduction of the duration of stimulation as well as the lower incidence of severe OHSS [8,9,10]. Meta-analysis by Griesinger et al showed similar benefits of GnRH analogs regarding PCOS populace [11].…”
Section: Introductionmentioning
confidence: 99%
“…After the demonstration of the partial inhibition of ovarian VEGF receptor 2 (VEGFR-2) phosphorylation levels by the dopamine agonist cabergoline in an animal model [35] and its consequent reversion of VEGFR-2 vascular permeability Cabergoline inhibits partially the VEGF receptor 2 phosphorylation levels and associated vascular permeability without affecting luteal angiogenesis [35] Reduction on the 'early'(within the first 9 days after hCG) onset of OHSS [36] Even using cabergoline, the OHSS incidence may be as high as 10.8% [36] Non-steroidal antiinflammatory A large RCT demonstrated that low dose aspirin was associated with reduction in the OHSS incidence (0.25% vs. 8.4%) in a high-risk group with similar pregnancy rates [37] Meloxican was capable of reducing the OHSS associated ovarian weight and expression of VEGF in an animal model [38] GnRH antagonist protocol This regimen is associated with a significant reduction in OHSS (Odds Ratio=0.60) as well as with fewer interventions to prevent OHSS (OR=0.43) However a slight reduction in pregnancy rates was also observed (OR=0.83) [39] Replacement of hCG A single dose of recombinant LH was safer than hCG and was effective in inducing follicular maturation The dosage of 15,000-30,000 IU is still too expensive [42] Using a GnRH agonist to induce final oocyte maturation, no cases of moderate/severe OHSS were observed in 1,152 cycles of oocyte donation against 14 cases in 1,137 cases who received hCG [43,44]. This requires the use of GnRH antagonist protocol.…”
Section: Dopamine Agonist Administrationmentioning
confidence: 92%
“…They are used after exogenous stimulation has begun and consequently shorten the total duration of treatment. A recent meta-analysis [39] reported a discreet worsening in pregnancy rates when GnRH antagonist regimens were compared to the standard long protocol (OR=0.83; 95% CI=0.72-0.95), and a significant reduction in severe OHSS was also reported (OR=0.60, 95% CI 0.40-0.88) as well as fewer interventions to prevent OHSS (OR=0.43, 95% CI 0.20-0.92). Additionally, when using GnRH antagonist protocols one may induce oocyte maturation with GnRH agonists, since this drug is not used to block pituitary secretion during ovarian stimulation.…”
Section: Gnrh Antagonist Protocolmentioning
confidence: 99%
“…Agonist yerine antagonist kullanılan siklularda da OHSS riski azalmaktadır. [42][43][44][45][46] Riskli hastalarda, agonist veya antagonist ile hipofizer süpresyon yapılırken, serum E2 düzeyi-nin hCG yapılabilir düzeye inmesi için, gonadotropin tedavisini kesmek (coasting) şiddetli OHSS riskini azaltmaktadır. 47 Bir diğer yöntem olan siklus iptalinde ise, hastaya hCG yapılmamaktadır.…”
Section: Yöneti̇munclassified